Analisis Transparansi dan Akuntabilitas dalam Pengelolaan Dana Zakat, Infaq, dan Shadaqah (ZIS) Pada LAZISNU Kota Medan - Aritonang, Solahuddin; Nasution, Yenni Samri Juliati; Nurwani, Nurwani (Ali Institute of Research and Publication, 2025)
This study aims to analyze transparency and accountability in the management of Zakat, Infaq, and Shadaqah (ZIS) funds at LAZISNU Medan City. The background of this study is the gap between the potential for large ZIS funds and the realization of revenues that are far below expectations, as well as the lack of public trust due to limited available information. Another problem found is the suboptimal management of funds, especially in aspects of financial reporting and publication of activities that have not been digitally integrated, making it difficult for the public to access. This type of research uses qualitative research with a descriptive approach, namely analyzing and classifying, investigating with survey techniques, interviews, and observations to review documents originating from sources. The results show that LAZISNU Medan City faces challenges in providing information that is easily accessible to the public, such as the lack of use of digital media to publish financial reports and activities, and the lack of an official website as a place to distribute information. In addition, constraints on human resources and information system management also affect the effectiveness of this institution's transparency and accountability. This study emphasizes the importance of strengthening policies, training, and improving technological infrastructure to support better management practices. This study can contribute to improving the governance of ZIS funds in zakat collection institutions. Keywords: Transparency, Accountability, ZIS Fund Management